Treatment of segmental tibial defects by bone transport with circular external fixation and a locking plate - Lu, Yao (J Int Med Res, 2020)
OBJECTIVE: To evaluate the effectiveness of bone transport involving circular external fixation and locking plate application for the treatment of segmental tibial defects. METHODS: A retrospective review of 12 patients with segmental tibial defects who underwent bone transport with circular external fixation and locking plate application. We evaluated external fixation time, external fixation index, time to achieve union, and complications. Clinical results were assessed using the Association for the Study and Application of the Methods of Ilizarov (ASAMI) score. Generic health-related outcome was assessed using the 36-Item Short-Form Health Survey questionnaire (SF-36). RESULTS: The mean follow-up was 25.8 months, and the mean defect size was 6.7 cm. All of the patients achieved union at the distraction callus and docking site. The average external fixation time was 299.5 days. The mean external fixation index was 16.5 days/cm, and the mean healing index was 44.9 days/cm. The functional outcomes were excellent in eight cases and good in four. The average SF-36 score was 92. CONCLUSION: Bone transport with external fixation and locking plate application may be a promising method for the treatment of segmental tibial defects.